O patronato Amazonense e o mundo do trabalho: a Revista da Associação Comercial e as representações acerca do trabalho no Amazonas (1908-1919) - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The Commercial Association of Amazonas (CAA) it was created in 1871, in one moment in that the patronage needed to place more pressure so much on the local State as well as on the concessionary companies of the public services. The objective was to assure economical advantages that guaranteed protection and to help against the foreign competition to improve the transport and to reduce the costs of the export of the eraser to the avid consuming markets of Europe. ACA was constituted like this as it legitimates representative of the interests of the patronage Amazonians before the society, producing a speech for your Magazine that sought to soften internal divergences and to organize strategies to assure the economical power and the political prestige of your members. Around the commercial institution the patronage, composed basically for the proprietors of the houses of trade, syringes owners and aviators, he knew how to elaborate an ideological project based on the uncertainties of the economy of the eraser at the beginning of the century XX and in the productive deficiency of the extrativismo of the eraser that guaranteed, above all, the largest control on the manpower adjusting her/ it to an organization model and efficiency based on the European models of production and I trade; that he/she had in the Portuguese element the ideal hard-working type, considered cheaper and orderly for the bourgeois pretensions. Seen by most of the authorities and of the bosses as an inferior class, the workers of the city of Manaus and mainly of the syringes of the interior they would be, according to the speeches of the Magazine of ACA (1908-1919), predisposed the vadiagem and to the mundane addictions for your rude and primitive nature, associated to the stigma of the indolence and of the incapacity of they manage your own lives. Therefore, it would be necessary that the patronage to act with the maximum of will and repression on the movements strikers and any other type of protest social expert as frolic act that disturbed your economical and political ambitions, even if such manifestations root justified for the poverty situation and hunger why still passed most of the workers in Belle Époque s called period
Keywords: História do trabalho; Movimentos sociais; História operária; Patronato; Work history; Social movements; Labor history, patronage; CIÊNCIAS HUMANAS: HISTÓRIA